ANALISIS PERAN NOTARIS DALAM PEMBUKTIAN DOKUMEN DAN PERJANJIAN DALAM HUKUM PERDATA - Ratnagung, Catur Galuh (Bhinneka Multidisiplin Journal, 2024)
The notary's role in legal documents has significant credentials to the practice of law and the interested parties involved in the transaction. Notaries not only witness the creation of documents and agreements, but are also responsible for validating, notarizing, and storing those documents. The presence of a notary is key in maintaining the validity and legal force of documents and agreements, providing legal certainty for the parties involved. This research aims to analyze the role of notaries in proving documents and agreements in civil law and identify related practical obstacles and applications. Qualitative research methods were used, involving in-depth interviews with experienced notaries and concrete case study analysis. The research results show that the role of notaries is very important in maintaining the integrity of the civil legal system by providing legal certainty and protecting the interests of the parties involved. However, challenges such as high costs and procedural complexity, as well as adaptation to technological developments and a dynamic legal environment, highlight the need for efforts to increase the accessibility of notary services and maintain high standards of professional ethics. Therefore, this research provides a basis for developing relevant and effective legal policies in strengthening the role of notaries as guardians of fair and effective legal certainty for society